Binary structures in Tuvan proverbs as a manifestation of the nationally marked vision of the world - Seliverstova, Elena I. (The New Research of Tuva, 2022)
Stable pairs of components called binomials or binary structures are frequently encountered in the paremiological space and are always examined as a pair. For Tuvan proverbs, they are crucial as well, since they can represent culturally valuable observations and landmarks. They also record the connections and dependencies existing in the world around them — such as the ones between labor and reward, the amount of effort and the result obtained, haste and its consequences, the raw material and the end product, etc. Binary structures are involved in the speakers' assessment of temporal representations – intervals, seasons, natural cycles, etc., they are part of the observations of the world of nature, the laws of which are projected onto the human world.Our study is based on an analysis of the paremies extracted by continuous sampling from the collections "Tuvan folk proverbs and sayings" (comp. by I. Plotkina and A. Kalzan), "Proverbs and sayings of the Tuvan people" (comp. by B. K. Budup), in some cases correlated with similar units in the Russian language as they appear in the "Grand dictionary of Russian proverbs", ed. by V. M. Mokienko.The analysis of binary structures has allowed us to outline ethnocultural terminology within the semantics of popular wisdom of proverbs. They stand for the uniqueness of culture, emphasize the importance of family ties and relationships, the value of friendship, and personal qualities socially significant for Tuvans.
Keywords: Tuvan language; linguistic world picture; paremia; proverbial binomial; ethno-marked originality; typology; value representations